Antioxidative and stable PdZn/ZnO/Al2O3 catalyst coatings concerning methanol steam reforming for fuel cell-powered vehicles. (15th June 2020) - Yan, Peijian; Tian, Pengfei; Cai, Cheng; Zhou, Shenghu; Yu, Xinhai; Zhao, Shuangliang; Tu, Shan-Tung; Deng, Chengwei; Sun, Yi
Graphical abstract: Highlights: Stable and antioxidative methanol steam reforming catalyst coating was prepared. A high Zn/Pd molar ratio is favorable for PdZn intermetallic compounds regeneration. Zn preferentially diffuses into PdH x NPs along PdH x 〈1 1 1〉 to form PdZn intermetallic compounds. Abstract: In the real application of on-board hydrogen production for proton exchange membrane fuel cell (PEMFC)-powered vehicles, catalysts promoting steam reforming of methanol (SRM) for hydrogen production suffer frequent oxidation considering how intermittently vehicles are driven. To address this challenge, PdZn/ZnO/Al2 O3 catalyst coatings with different molar ratios were prepared by the co-reduction method. The results showed a favorable effect of the high molar ratio of Zn to Pd on regenerating the PdZn intermetallic compounds by reducing the oxidized catalysts. This is because Zn atoms preferentially diffused into PdH x NPs along the PdH x 〈1 1 1〉 direction to form PdZn intermetallic compounds, and a high molar ratio of Zn to Pd guaranteed abundant Zn atoms along PdH x 〈1 1 1〉 direction during the reduction process. The oxidized PdZn/ZnO/Al2 O3 catalyst coatings gradually recovered their catalytic activity due to the regeneration of PdZn intermetallic compounds. The PdZn/ZnO/Al2 O3 catalyst coatings showed better stability than the reported catalysts and an excellent antioxidation ability in the SRM reaction, suggesting great potential for the on-board production of hydrogen for PEMFC-powered vehicles if coupled with a high-temperature water-gas shift reactor.